Utilization of The Place of Delivery Based on Childbirth Assurance and Community Habits - Mareta Bakale Bakoil; Heru Santoso Wahito Nugroho; Veki Edizon Tuhana (Humanistic Network for Science and Technology (HNST), 2019)
Background: Phenomenon in Indonesia is still many mothers gave birth are not using health facilities and helped by traditional birth attendants (TBA), which can have an impact on high maternal mortality. South Central Timor Districts is one of regencies in East Nusa Tenggara Province with the highest maternal mortality rate is 290/100,000 live births. Methods: The type of this research was observational analytic with cross sectional design. The sample zize was 95 respondents, selected using systematic random sampling. The categorical data were analyzed using descriptive statistics in the form of frequency and percentage, then analyzed using Chi-square test and logistic regression test. Results: The p-value of childbirth assurance was 0.003 (OR 0.098, 95% CI: 0.019 to 0.509), the p-value of the distance of residence was 0.498 (OR 1.822 95% CI 0.428 to 7.761), p-value of the travel time was 0.710 (OR 1.292 95% CI 0.299 to 5.583), the p-value of customs of the people in choosing the place of labor was 0.010 (13.833 OR 95% CI 2.282 to 83.861). The result of logistic regression test showed that childbirth assurance and customs of the people in choosing where labor was the strongest determinant to use birth place. Conclusion: Childbirth assurance and community habits in choosing the place of delivery had a significant correlation with the use of delivery place. While the distance of residence and travel time are not significant to the use of delivery place. Keywords: place of delivery; childbirth assurance; community habits